2006
DOI: 10.1016/j.jorganchem.2006.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of methylbismuth(III) complexes containing dithio ligands: 2. Crystal and molecular structure of [MeBiCl(S2CNEt2)] and transformation of some to Bi2S3

Abstract: Reactions of methylbismuth(III) dichloride with sodium salts of dithiocarbamates have been carried out in 1:1 and 1:2 stoichiometric ratios in anhydrous benzene to yield products of the types [MeBiCl(S 2 CNR 2 )] [where R = Me (1), Et (2) and i Pr (3)] and,andThese complexes were characterized by elemental analyses and by FT-IR and NMR ( 1 H and 13 C) spectra. The X-ray structure of [MeBiCl(S 2 CNEt 2 )] (2), indicates the presence of unique BiÁ Á ÁClÁ Á ÁBi secondary bonds resulting in a distorted square pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…6, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] It is almost certain that the conversion to nanoparticles in these systems involves prior coordination of the S-based ligand, and decomposition of preassembled sulfur-containing bismuth(III) complexes may afford some advantages in control over the shape and size of the particles formed. [15][16][17][18][19][20][21] Bismuth(III) routinely adopts coordination numbers higher than six and stable aminopolycarboxylate (APC) and polyaminopolycarboxylate (PAPC) complexes that also contain sulfur-based ligands have been reported. 29 Tian et al 15 have recently reported a colloidal solution method to prepare Bi 2 S 3 nanorods and dandelion-like nanostructures from Bi(SCOPh) 3 in binary surfactant systems at 150 °C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] It is almost certain that the conversion to nanoparticles in these systems involves prior coordination of the S-based ligand, and decomposition of preassembled sulfur-containing bismuth(III) complexes may afford some advantages in control over the shape and size of the particles formed. [15][16][17][18][19][20][21] Bismuth(III) routinely adopts coordination numbers higher than six and stable aminopolycarboxylate (APC) and polyaminopolycarboxylate (PAPC) complexes that also contain sulfur-based ligands have been reported. 29 Tian et al 15 have recently reported a colloidal solution method to prepare Bi 2 S 3 nanorods and dandelion-like nanostructures from Bi(SCOPh) 3 in binary surfactant systems at 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Uniform Bi 2 S 3 flowers with a size of 3−5 μm composed of nanowires with a diameter of 80 nm can be prepared from BiCl 3 and acetothioamide in the presence of the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate . Other strategies to produce Bi 2 S 3 nanostructures have been described. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth complexes used for the synthesis of Bi 2 S 3 nanostructures include bismuth(III) thioacetates [Bi(SCOPh) 3 ], pyridine and 1,10-phenanthroline adducts of bismuth(III) dithioxanthate complexes [Bi(S 2 COCH(CH 3 )CH 2 CH 3 ) 3 ], bismuth(III) di- n -octyl-dithiophosphate [Bi(S 2 P(OC 8 H 17 ) 2 ) 3 ], , bismuth(III) diethyldithiocarbamate complexes, bismuth(III) thiourea [Bi 6 (pydc) 8 (Hpydc) 2 (tu) 8 ], and bismuth(III) thiocarbazide {[Bi 2 (pydc) 3 (tsc)(H 2 O) 2 ]·H 2 O} ∞ complexes . Most of these single source precursors produced nanorods or nanotubes with various lengths and diameters.…”
Section: Binary Chalcogenidesmentioning
confidence: 99%
“…Dithiolato moieties like dithiocarbamates1–6 and alkylene‐ dithiophosphates7–11 are versatile ligands and display a broad variety of coordination patterns, leading to a great diversity of molecular and supramolecular structures. With regards to structural studies, these ligands often display bidentate coordination patterns, which may be isobidentate (symmetrical) or anisobidentate (unsymmetrical) both in chelating and bridging situations.…”
Section: Introductionmentioning
confidence: 99%